Irrigation return flow causing a nitrate hotspot and denitrification imprints in groundwater at Tinwald, New Zealand - M. K. Stewart; M. K. Stewart; P. L. Aitchison-Earl (Hydrology and Earth System Sciences, 2020)
Nitrate concentrations in groundwater have been historically high (N≥11.3 mg L−1) in an area surrounding Tinwald, Ashburton, since at least the mid-1980s. The local community is interested in methods to remediate the high nitrate in groundwater. To do this, they need to know where the nitrate is coming from. Tinwald groundwater exhibits two features stemming from irrigation with local groundwater (i.e. irrigation return flow). The first feature is increased concentrations of nitrate (and other chemicals and stable isotopes) in a “hotspot” around Tinwald. The chemical concentrations of the groundwater are increased by recirculation of water already relatively high in chemicals. The irrigation return flow coefficient C (irrigation return flow divided by irrigation flow) is found to be consistent with the chemical enrichments. The stable isotopes of the groundwater show a similar pattern of enrichment by irrigation return flow of up to 40 % and are also enriched by evaporation (causing a loss of about 5 % of the original water mass). Management implications are that irrigation return flow needs to be taken into account in modelling of nitrate transport through soil–groundwater systems and in avoiding overuse of nitrate fertiliser leading to greater leaching of nitrate to the groundwater and unnecessary economic cost. The second feature is the presence of “denitrification imprints” (shown by enrichment of the δ15N and δ18ONO3<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="43pt" height="18pt" class="svg-formula" dspmath="mathimg" md5hash="18d502ce97b90c69fd2d0061c918c7e5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="hess-24-3583-2020-ie00001.svg" width="43pt" height="18pt" src="hess-24-3583-2020-ie00001.png"/></svg:svg> values of nitrate) in even relatively oxic groundwaters. The denitrification imprints can be clearly seen because (apart from denitrification) the nitrate has a blended isotopic composition due to irrigation return flow and N being retained in the soil–plant system as organic N. The nitrate concentration and isotopic compositions of nitrate are found to be correlated with the dissolved oxygen (DO) concentration. This denitrification imprint is attributed to localised denitrification in fine pores or small-scale physical heterogeneity where conditions are reducing. The implication is that denitrification could be occurring where it is not expected because groundwater DO concentrations are not low.